Evaluasi Pelaksanaan Asesmen Nasional Tahun 2021 - Usar Naely; Lukman Asha; Beni Azwar; Jumira Warlizasusi; Sumarto Sumarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT The National Assessment is a program to assess the quality of each school, madrasah, and equality program at the primary and secondary levels. Research with qualitative descriptive type that describes or describes a phenomenon, using the CIPP evaluation method (Context, Input, Process and product). The data sources used are primary data sources and secondary data sources. Data collection techniques through the methods: 1) Interview, 2) Observation, 3) documentation. The results of this study are (1) the implementation of the National Assessment at SMA Negeri 4 Rejang Lebong needs to be evaluated because through this evaluation the school can correct deficiencies and overcome obstacles encountered during implementation. (2) Condition of infrastructure facilities and infrastructure at SMA Negeri 4 Rejang Lebong in fulfilling the requirements to support the implementation of the 2021 National Assessment has referred to the technical guidelines (juknis) for the 2021 ANBK implementation set by the Central Level Executor; (3) The implementation of AKM at SMA Negeri 4 Rejang Lebong runs according to schedule, for 2 days, namely on 27-28 September 2021, it is appropriate and follows the Standard Operating Procedures (POS) of the National Assessment in 2021. (4) Obstacles that occur in the implementation of the assessment the minimum competencies at SMA Negeri 4 Rejang Lebong are the absence of several students during the simulation, the lack of knowledge of teachers and students about the functions and objectives of the national assessment; (5) Several solutions were carried out to overcome obstacles in the implementation of the minimum competency assessment at SMA Negeri 4 Rejang Lebong, namely participating in the National Assessment workshop, utilizing the guru.Id account in learning, besides that all school elements strive to improve the education system through achievement indicators. Education report card for SMA Negeri 4 Rejang Lebong to serve as a forum for remedial measures for the implementation of AKM in 2021 and as a reference for preparation for AKM in 2022Keywords: National Assessment, quality, evaluation ABSTRAK Asesmen Nasional adalah program penilaian terhadap mutu setiap sekolah, madrasah, dan program kesetaraan pada jenjang dasar dan menengah. Penelitian dengan jenis deskriptif kualitatif yang mendeskripsikan atau menggambarkan suatu fenomena, dengan menggunakan metode evaluasi CIPP ( Konteks, Input, Proses dan produk ). Sumber data yang digunakan adalah sumber data primer dan sumber data sekunder. Tehnik pengumpulan data melaui metode : 1) Wawancara, 2) Observasi, 3) dokumentasi. Hasil dari penelitian ini adalah (1) Pelaksanaan Asesmen Nasional di SMA Negeri 4 Rejang Lebong perlu di evaluasi karena melalui evaluasi tersebut sekolah dapat memperbaiki kekurangan dan mengatasi hambatan yang ditemui pada saat pelaksanaan.(2) Kondisi sarana dan prasarana infra struktur pada SMA Negeri 4 Rejang Lebong dalam memenuhi persyaratan untuk mendukung pelaksanaan Asesmen Nasional tahun 2021 sudah mengacu pada petunjuk teknis (juknis) pelaksanaan ANBK tahun 2021 yang ditetapkan oleh Pelaksana Tingkat Pusat; (3) Pelaksanaan AKM di SMA Negeri 4 Rejang Lebong berjalan sesuai jadwal, selama 2 hari yaitu pada tanggal 27-28 september 2021 sudah sesuai dan mengikuti Prosedur Operasional Standar (POS) Asesmen Nasional tahun 2021. (4) Hambatan yang terjadi dalam pelaksanaan asesmen kompetensi minimum di SMA Negeri 4 Rejang Lebong yaitu ketidakhadiran beberapa siswa pada saat simulasi , minimnya pengetahuan guru dan siswa terhadap fungsi dan tujuan Asesmen nasional; (5) Beberapa solusi yang di lakukan untuk mengatasi kendala dalam pelaksanaan asesmen kompetensi minimum di SMA Negeri 4 Rejang Lebong yaitu mengikuti kegiatan workshop Asesmen Nasional,pemanfaatan akun guru.Id dalam pembelajaran, selain itu semua elemen sekolah berupaya untuk memperbaiki sistem pendidikan melalui indikator capaian Rapor Pendidikan SMA Negeri 4 Rejang Lebong guna menjadi wadah remidi terhadap pelaksanaan AKM tahun 2021 dan menjadi acuan persiapan menghadapi AKM tahun 2022 Kata Kunci: Asesmen Nasional, mutu, evaluasi